Estudo da eletro-oxidação do paracetamol utilizando um reator eletroquímico em fluxo com eletrodo de diamante dopado com boro - Veroli, Alyne Bernardes (Universidade Federal de São Carlos, 2017)
This study was carried out with the aid of an experimental design, using a solution of paracetamol containing 100 mg L -1 of initial total organic carbon (TOC initial ) in 0.1 mol L -1 Na 2 SO 4 of ionic strength and a flow rate of 8.0 L min -1 . After the statistical treatment, analyzing the obtained values of rate constant of mineralization, k(TOC rel ) and average energy consumption for removing 50% TOC rel , AEC 50 as responses, the significant variables and coefficients were determined for each one of these responses. From the response surface generated for k(TOC rel ), the experimental conditions for the highest values of k(TOC rel ) were: current density in the range of 180 to 200 mA cm -2 , temperature in the range of 50 to 55 °C and intermediate pHs (4 to 12). For the response of AEC 50 , their lowest values in the generated surface were obtained for: current density up to 40 mA cm -2 , temperature in the range of 15 to 45 °C and pH in the range of 2 to 10. As these two different responses led to very wide ranges of experimental parameters, the desirability function was used in order to establish an optimized set of experimental conditions. With this procedure, the yielded parameters (current density of 114 mA cm -2 , temperature of 51.8 °C and pH of 7.45) led to predicted values of k(TOCrel) and AEC 50 of 0.0183 ± 0.0032 min -1 and 150.5 ± 24.9 kW h kg -1 , respectively. For purely practical reasons, the following experimental conditions were adopted: current density of 100 mA cm -2 , temperature of 50 °C and pH 7. In these conditions, a significant improvement in the paracetamol electrooxidation kinetics was observed, for all investigated flow rates, when a turbulence promoter was introduced in the electrochemical reactor. Using a flow rate of 6 L min -1 , the obtained values of k(TOC rel ), AEC 80 and electric charge for removing 80% TOC, Q 80 were: 0.0295 min -1 , 209.1 kW h kg -1 (13.9 kW h m -3 ) and 1.33 A h L -1 , respectively. In the absence of the turbulence promoter and using the same flow rate, the obtained values of these same quantities were: 0.0118 min -1 , 365.13 kW h kg -1 (27.2 kW h m -3 ) and 3.33 A h L -1 , respectively.
Study of the electrooxidation of paracetamol using a flow electrochemical reactor with a boron-doped diamond electrode
Keywords: Eletro-oxidação; Promotor de turbulência; Planejamento fatorial; Paracetamol; Eletrooxidation; CIENCIAS EXATAS E DA TERRA::QUIMICA; ENGENHARIAS::ENGENHARIA SANITARIA::TRATAMENTO DE AGUAS DE ABASTECIMENTO E RESIDUARIAS::ESTUDOS E CARACTERIZACAO DE EFLUENTES INDUSTRIAIS; ENGENHARIAS::ENGENHARIA SANITARIA::TRATAMENTO DE AGUAS DE ABASTECIMENTO E RESIDUARIAS::PROCESSOS SIMPLIFICADOS DE TRATAMENTO DE AGUAS